Bladder cancer and occupational exposure to leather. Issue 2 (February 1986) - Marrett, L D; Hartge, P; Meigs, J W
Abstract : A large case-control study of bladder cancer (2982 cases; 5782 controls) included information about occupational exposure to leather. Occupational histories of exposed white study subjects were reviewed and 150 were determined to have had "true" on the job exposure to leather. The odds ratio estimate (OR) of bladder cancer associated with such exposure in white subjects (n = 8063) was 1.4 (95% confidence limits = 1.0, 1.9) after adjustment for sex, age, and cigarette smoking. The risk was highest in those first employed in a leather job before 1945, although no dose-response relation with duration of leather employment was found. Subjects employed in "dusty" leather jobs had a slightly higher risk than those with other types of leather jobs. Our results are consistent with reports of an increased risk of bladder cancer associated with exposure to leather. Although the agents responsible have not been identified, our findings of an increased risk associated with exposure in the earlier years of this century and in dusty jobs suggest that leather dusts may be important.